2007
DOI: 10.1111/j.1523-5378.2007.00576.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Helicobacter pylori Therapy from a Meta‐analytical Perspective

Abstract: Even before the discovery of Helicobacter pylori as their cause, chronic gastritis and peptic ulcer disease were empirically treated with anti-infectious agents. However, it was not until that finding that an antibiotic approach began to be used systematically. The main aim of this article is to review the evolution of H. pylori therapy from a meta-analytical perspective. Initially, antibiotic monotherapy had a minor efficacy on H. pylori. Dual therapy including either bismuth compounds or proton-pump inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
48
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 54 publications
0
48
0
Order By: Relevance
“…However, concerns have been expressed regarding the progressive reduction of its efficiency over the past years [6], possibly due to the development of antimicrobial resistance, particularly in the United States and Europe [7,8]. Resistance is variable from country to country, and also within different regions of the same country [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, concerns have been expressed regarding the progressive reduction of its efficiency over the past years [6], possibly due to the development of antimicrobial resistance, particularly in the United States and Europe [7,8]. Resistance is variable from country to country, and also within different regions of the same country [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Consensus conferences have recommended therapeutic regimens that achieve H pylori cure rates higher than 80% on an intention-to-treat basis [1][2][3] . However, several large clinical trials and metaanalyses have shown that the most commonly used firstline therapies-including proton pump inhibitors (PPIs) plus two antibiotics-may fail in up to 20% of patients [4,5] , and in the clinical routine setting, the treatment failure rate might be even higher. Moreover, during the last few years, the efficacy of PPI-based regimens seems to be decreasing, and several studies have reported intention-to-treat eradication rates lower than 75% [6][7][8][9][10][11][12][13][14] and even lower than 50% [15,16] .…”
Section: Introductionmentioning
confidence: 99%
“…Failure to cure H. pylori infection has been noted for more than 20 to 30% of patients (37). In addition, several studies have found an eradication rate lower than 75% (6,11,59), and values as low as 25 to 45% have also been recently reported (22,24). Thus, prolonged standard triple therapy for up to 2 weeks has been recommended (9,23,34), and in cases of eradication failure, a quadruple therapy with a proton pump inhibitor, bismuth salt, tetracycline, and metronidazole has been advised as a second-line therapy (8,13,44).…”
mentioning
confidence: 99%